Meta-analysis of operative experiences of general surgery trainees during training - Elsey, E.J.; Griffiths, G.; Humes, D.J.; West, J. (Wiley, 2016)
BACKGROUND: General surgical training curricula around the world set defined operative numbers to be achieved before completion of training. However, there are few studies reporting total operative experience in training. This systematic review aimed to quantify the published global operative experience at completion of training in general surgery.